Buriano Castro, Ana. (2023). Catolicismo, espacio público y política en Ecuador, siglo XIX. Universidad Andina Simón Bolívar, sede Ecuador; Corporación Editora Nacional. - Aguirre Pacheco, Katiushka (2025)
This review examines a book that compiles seven texts by Ana Bejarano Castro on “garcian” conservative thought, focusing on Ecuadorian President Gabriel García Moreno and his nineteenth-century political project. Published in January 2023, the volume opens with an introductory study that situates the author’s intellectual trajectory and historiographical method, emphasizing the press as a source to trace political participation and the construction of legitimacy. The chapters are organized into three sections: the legitimization of Garcian conservatism, intellectual production as a device for national preservation, and the clergy’s role within the state project and its normative challenges. The book offers a critical rereading of conservative discourses tied to Garcianism, highlighting their evolution, diversity, and legal–institutional articulation within Ecuador’s republican context.